Defining the structural basis for human alloantibody binding to human leukocyte antigen allele HLA-A*11:01 - Gu, Yue (2019)
Our understanding of the conformational and electrostatic determinants that underlie targeting of human leukocyte antigens (HLA) by anti-HLA alloantibodies is principally based upon in silico modelling. Here we provide a biochemical/biophysical and functional characterization of a human monoclonal alloantibody specific for a common HLA type, HLA-A*11:01. We present a 2.4 Å resolution map of the binding interface of this antibody on HLA-A*11:01 and compare the structural determinants with those utilized by T-cell receptor (TCR), killer-cell immunoglobulin-like receptor (KIR) and CD8 on the same molecule. These data provide a mechanistic insight into the paratope−epitope relationship between an alloantibody and its target HLA molecule in a biological context where other immune receptors are concomitantly engaged. This has important implications for our interpretation of serologic binding patterns of anti-HLA antibodies in sensitized individuals and thus, for the biology of human alloresponses.